The ancient novel and the frontiers of genre - Futre Pinheiro, M. (Marília); Schmeling, Gareth L.; Cueva, Edmund P., 1964- (Ancient narrative. Supplementum, 2014)
"This volume presents a collection of thirteen papers from the Fourth International Conference on the Ancient Novel (ICAN 2008), which was held in Lisbon at the Fundação Calouste Gulbenkian from July 21 to 26, 2008.